2019
DOI: 10.3390/jcm9010019
|View full text |Cite
|
Sign up to set email alerts
|

Co-Morbidities and Sex Differences in Long-Term Quality-of-Life Outcomes among Patients with and without Diabetes after Total Knee Replacement: Five-Year Data from Registry Study

Abstract: Improved understanding of quality-of-life (QoL) outcomes can provide valuable information on intervention effectiveness and guide better patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Diabetes mellitus was found to related with poor quality of life. Similar to our study results, after total knee replacement surgery, patients with diabetes were found to exhibit poor quality life scores than patients without diabetes (29). Patients with diabetes usually reacts with aggression predisposition which leads to loss of social support, furthermore sleep disorders and mental comorbidity are associated with lower quality of life in patients with diabetes (30).…”
Section: Discussionsupporting
confidence: 87%
“…Diabetes mellitus was found to related with poor quality of life. Similar to our study results, after total knee replacement surgery, patients with diabetes were found to exhibit poor quality life scores than patients without diabetes (29). Patients with diabetes usually reacts with aggression predisposition which leads to loss of social support, furthermore sleep disorders and mental comorbidity are associated with lower quality of life in patients with diabetes (30).…”
Section: Discussionsupporting
confidence: 87%
“…In the study by Snell et al 17 , the most common comorbidities were musculoskeletal conditions, such as arthritis in other joints and other musculoskeletal pain, cardiovascular conditions, such as hypertension, and coronary heart disease. Additionally, Tew et al 45 showed that one-fifth of the patients who underwent TKA developed diabetes. Patients with diabetes, especially women, showed a significantly lower QoL than those without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal disorders and injuries that are characterized by sexual dimorphism are not routinely considered by orthopedic surgeons when making treatment decisions [ 25 ]. This is surprising as sex differences in patient-related outcomes and functionality after orthopedic surgery are well described in the literature [ 26 , 27 , 28 , 29 ]. This observation might partly be caused by sex-specific postoperative morbidity and mortality [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%